2021
DOI: 10.1111/acel.13304
|View full text |Cite
|
Sign up to set email alerts
|

Mtor inhibition by INK128 extends functions of the ovary reconstituted from germline stem cells in aging and premature aging mice

Abstract: Stem cell transplantation has been generally considered as promising therapeutics in preserving or recovering functions of lost, damaged, or aging tissues. Transplantation of primordial germ cells (PGCs) or oogonia stem cells (OSCs) can reconstitute ovarian functions that yet sustain for only short period of time, limiting potential application of stem cells in preservation of fertility and endocrine function. Here, we show that mTOR inhibition by INK128 extends the follicular and endocrine functions of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…On the other hand, an in vivo experiment in mice observed that permutation transcripts were closely associated with mitochondrial and ovarian abnormalities (86). mTOR is closely related to the metabolic process of mitochondria in ovarian cells (87), and inhibition of mTOR significantly improved follicular development and endocrine functions of the ovaries, thereby extending reproductive aging and premature aging of POF mice (88). These observations suggested that abnormal FMR1 transcription potentially causes…”
Section: Fragile X Messenger Ribonucleoprotein 1 (Fmr1)mentioning
confidence: 90%
“…On the other hand, an in vivo experiment in mice observed that permutation transcripts were closely associated with mitochondrial and ovarian abnormalities (86). mTOR is closely related to the metabolic process of mitochondria in ovarian cells (87), and inhibition of mTOR significantly improved follicular development and endocrine functions of the ovaries, thereby extending reproductive aging and premature aging of POF mice (88). These observations suggested that abnormal FMR1 transcription potentially causes…”
Section: Fragile X Messenger Ribonucleoprotein 1 (Fmr1)mentioning
confidence: 90%
“…However, the majority of PGCs enter meiosis and undergo folliculogenesis soon after transplantation, and proliferative PGCs and meiocytes disappear about six weeks following transplantation [ 270 ]. Encouragingly, mTOR inhibition by INK128 improves and extends the reconstituted ovarian and endocrine functions in reproductive aging and premature aging mice [ 271 ].…”
Section: Ovarian Aging Intervention Strategymentioning
confidence: 99%
“…The ovary has two main roles: the female reproductive organ and a hormone secretion system. The ovaries function cyclically; in humans, their function declines with age from the mid-30s, and their menopause-disrupting endocrine function starts in the mid-50s [ 1 ]. Ovarian function declines early relative to other organs in the body and is implicated in predicting ovarian menopause [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study focused on preventing pathological changes in ovarian cells by mTOR inhibition, which postponed follicular activation and development and extended the follicle reserve and endocrine function of the ovaries [ 1 ]. Additionally, ovarian fibrosis in stromal interstitial tissues surrounding follicles is a key causal factor of obesity-induced ovarian dysfunction and the process is similar to that of reproductive aging [ 17 ].…”
Section: Introductionmentioning
confidence: 99%